Intestinal Epithelial Cell-Related Alternative Splicing Events in Dextran Sodium Sulfate-Induced Acute Colitis - Lin, Xiaoning; Zheng, Bijuan; Gu, Feiteng; Fan, Xin; Shen, Jianlin (Turkish Journal of Gastroenterology, 2023)
Background: Alternative splicing of pre-messenger RNA is recognized as the crucial mechanism for gene expression regulation and proteome diversity generation. Alternative splicing has been found to be related to the pathogenesis of inflammatory bowel disease. The aim of this study was to identify the alternative splicing events in intestinal epithelial cells from mouse models of acute colitis and expand the understanding of the pathogenesis of inflammatory bowel disease. Methods: The acute colitis mouse models were constructed, and intestinal epithelial cells of the colon were isolated for RNA sequence. The replicate Multivariate Analysis of Transcript Splicing software was used to analyze the alternative splicing events. The functional analysis was performed on genes with significant differential alternative splicing events. The alternative splicing events of picked genes were validated by reverse transcription polymerase chain reaction. Results: A total of 340 significant differential alternative splicing events (from 293 genes) were screened out in acute colitis, and the alternative splicing events of CDK5-regulatory subunit associated protein 3 and TRM5 tRNA methyltransferase 5 were validated. The functional analysis showed that differential alternative splicing events in acute colitis participate in the apoptotic process, and the alternative splicing events of 3 genes (BCL2/adenovirus E1B-interacting protein 2, tumor necrosis factor receptor-associated factor 1, and tumor necrosis factor receptor-associated factor 7) were validated by reverse transcription polymerase chain reaction. Conclusion: This study pointed out the potential impact of different alternative splicing in acute colitis. Cite this article as: Lin X, Zheng B, Gu F, Fan X, Shen J. Intestinal epithelial cell-related alternative splicing events in dextran sodium sulfate-induced acute colitis. Turk J Gastroenterol. 2023;34(5):490-496.